Electro-Acupuncture Alleviates Chronic Unpredictable Stress-Induced Depressive- and Anxiety-Like Behavior and Hippocampal Neuroinflammation in Rat Model of Depression - Yue, Na; Li, Bing; Yang, Liu; Han, Qiu-Qin; Huang, Hui-Jie; Wang, Ya-Lin; Wang, Jing; Yu, Rui; Wu, Gen-Cheng; Liu, Qiong; Yu, Jin (Frontiers in Molecular Neuroscience, 2018)
Depression is the second leading cause of disability worldwide. The effects of clinical depression may be mediated by neuroinflammation such as activation of microglia and high levels of proinflammatory cytokines in certain brain areas. Traditional Chinese medicine techniques such as electro-acupuncture (EA) are used extensively in Asia to treat mental health disorders. However, EA has not been rigorously studied in treatment of depression. This study was designed to assess the effectiveness of EA on depressive-like behavior and explore the role of hippocampal neuroinflammation in the potential antidepressant effect of EA. In this study, we used 6 chronic unpredictable stressors daily in a random sequence for 10 weeks. EA were performed on ‘Bai-Hui’ (Du-20) (+) and ‘Yang-Ling-Quan’ (GB-34, the right side) (−) acupoints by an EA apparatus (HANS Electronic Apparatus, LH202H, 2\100Hz, 0.3 mA) for 30 mins once every other day for last 4 weeks. The behavior tests including open field test and forced swimming test, which are widely used to assess depressive and anxiety-like behavior were performed on the Monday and Tuesday of the eleventh week. The results showed that ten week of chronic unpredictable stress (CUS) caused behavioral deficits in rats and neuroinflammation in hippocampus, such as increased expression of NLRP3 inflammasome components, upregulated mRNA level of IL-1β and the protein level of IL-1β mature form (p17) and activation of microglia. Moreover, four weeks of EA treatment significantly attenuated behavioral deficits caused by CUS. EA’s antidepressant effect was accompanied by markedly decreased expression of certain NLRP3 inflammasome components and matured IL-1β. Meanwhile, EA treatment can significantly reverse CUS-induced increases in P2X7 receptor, Iba-1, IL-18, TNFα and IL-6 expression and decreases in GFAP expression. In conclusion, EA exhibited the antidepressant effect and alleviated the hippocampal neuroinflammation. These findings may provide insight into the role of hippocampal neuroinflammation in the antidepressant effect of EA. Key Words: depression; EA; chronic unpredictable stress; IL-1β; P2X7 receptor; glia